(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
The literature available from past to modern times clearly signifies that the property of Pushpadhanwa rasa was used for Vrisya (aphrodisiac), Vajikarana (Increased sexual power), Vandhyatwa (sterility in both male and female). It was a preparation that can be used for male infertility due to oligospermia and female infertility due to Ovarin cyst. It firstly came into existence around 9th century depicted by Acharya Bahata followed by literatures like Rasa Ratna Sammuchaya, Yoga Tarangini, Bruhat Yoga Tarangini, Yogaratnakar, Rasa Tarangini, Bhaishjya Ratnavali etc was practicing these formulations to their patients. In this paper the developmental sequence of Pushpadhanwa rasa was deeply studied. An honest attempt has made to establish the periodical revolution of Pushpadhanwa rasa in the field of Vajikarana Chikistha. In this paper a good collection of Pushpdhanwa Rasa which could be utilized to prepare as per the need and use it clinically.